Revije pri posredovanju slovenske književnosti v italijanski kulturni prostor - Jan, Zoltan (Slavistična revija, 2006)
Using concrete examples of reception of Slovene poets and writers (e.g., Edvard Kocbek, Ivan Cankar), the article discusses the significance of journalistic publications and analyzes the connections between some transmitters of Slovene literature into Italian cultural sphere (e.g., Jolka Milič, Ciril Zlobec). It concludes witha a look at the diversity of Italian journals.
Keywords: Alojz Rebula; Boris Pahor; Cankar, Ivan; Ciril Zlobec; Edvard Kocbek; Italian journals; italijanske revije; Ivan Cankar; Jolka Milič; Kocbek, Edvard; literarni stiki; literary contacts; Marija Pirjevec; Milič, Jolka; Miran Košuta; Slovene literature; Slovene poets; Slovene writers; slovenska književnost; slovenski pesniki; slovenski pisatelji; Zlobec, Ciril